2018
DOI: 10.1093/femsre/fuy004
|View full text |Cite
|
Sign up to set email alerts
|

The human cytomegalovirus terminase complex as an antiviral target: a close-up view

Abstract: Human cytomegalovirus (HCMV) is responsible for life-threatening infections in immunocompromised individuals and can cause serious congenital malformations. Available antivirals target the viral polymerase but are subject to cross-resistance and toxicity. New antivirals targeting other replication steps and inducing fewer adverse effects are therefore needed. During HCMV replication, DNA maturation and packaging are performed by the terminase complex, which cleaves DNA to package the genome into the capsid. Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 66 publications
0
63
0
3
Order By: Relevance
“…Letermovir is unique in that the mechanism of action targets the CMV terminase complex instead of the viral DNA polymerase that current drugs target. 70,71 While letermovir is not approved for use in cCMV and dosing is not available, novel ways to approach treatment for these infants are on the horizon.…”
Section: Treatmentmentioning
confidence: 99%
“…Letermovir is unique in that the mechanism of action targets the CMV terminase complex instead of the viral DNA polymerase that current drugs target. 70,71 While letermovir is not approved for use in cCMV and dosing is not available, novel ways to approach treatment for these infants are on the horizon.…”
Section: Treatmentmentioning
confidence: 99%
“…Letermovir, a CMV antiviral drug that was recently US Food and Drug Administration (FDA)‐approved, acts late in the CMV replication cycle by inhibiting the CMV DNA terminase complex. The main function of the terminase complex is to cleave CMV DNA concatemers into single units of functional CMV genomes …”
Section: Virologymentioning
confidence: 99%
“…The main function of the terminase complex is to cleave CMV DNA concatemers into single units of functional CMV genomes. 23,24 CMV glycoprotein B (gB), which is encoded by the UL55 gene, 25 accounts for more than 50% of the protein mass of the CMV envelope. A common method of CMV genotyping is based on variations in the UL55 gene.…”
Section: Virologymentioning
confidence: 99%
“…Mechanistic studies and the localization of resistance mutations suggested that this drug essentially interacts with the pUL56 subunit of the viral terminase complex (pUL89-pUL56) [6][7][8]. However, resistance observed both in pUL56 and pUL89 and proximity of the selected UL89 and UL56 mutations suggests that letermovir targets a functional locus involving pUL56 and pUL89 interaction [9]. The lack of structural and functional data must be filled to better understand the letermovir mechanism and design additional drugs or peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The HCMV terminase complex (pUL89-pUL56) is a critical component of the DNA-packaging machinery which aims to translocate a unit of viral DNA genome into an empty capsid [9]. These proteins are partially characterized through their homology with HSV-1 pUL15 and pUL28, which have an essential role in HSV-1 genome packaging.…”
Section: Introductionmentioning
confidence: 99%